Keragaan Karakter Agronomi Padi Hibrida Baru - Nita Kartina; Yuni Widyastuti; Satoto Satoto (Buletin Plasma Nutfah, 2014)
Agronomic Characters of New Hybrid Rice. Nita Kartina, Yuni Widyastuti, and Satoto. Hybrid rice is the F1 generation derived from the crossing between cytolasmic genetic male sterile and restorer as two parental line. Development of hybrid rice technology obtained throught heterosis This research has the aim was to assess the agronomy characters of some new hybrid rice. Four hundred of Indonesia Center of Rice Research (ICRR) new hybrids rice selected based on yield and phenotipic performances. The activitity conducted in Sukamandi field West Java Province in wet season 2012. The research was arranged in an augmented design that divided in to seven blocks. Each block consist of 20 hybrid rice and five check such as Mapan P.05, Inpari 13, Dodokan, Ciherang, and Hipa 8. There are fourteen hybrids rice showed good agronomic characters and has higher heterosis standard than Ciherang and Hipa 8. Four hybrid rice combinations give the result that significantly different than Ciherang (5.59 t/ha) as check variety. Those hybrids are GMJ11/CRS777 (9.1 t/ha), GMJ12/CRS707 (7.6 t/ha), GMJ13/CRS703 (8.7 t/ha), and GMJ12/CRS795 (7.95 t/ha). AbstrakPadi hibrida merupakan generasi F1 hasil persilangan antara galur mandul jantan sebagai tetua betina dan galur pemulih kesuburan sebagai tetua jantan. Teknologi padi hibrida dihasilkan melalui pemanfaatan heterosis. Penelitian ini bertujuan untuk mengkaji keragaan agronomi sejumlah padi hibrida baru. Sebanyak 400 padi hibrida baru rakitan Balai Besar Penelitian Tanaman Padi diseleksi berdasarkan daya hasil dan penampilan fenotipik di lapangan menggunakan analisis augmented. Penelitian dilakukan di Kebun Percobaan Sukamandi, Jawa Barat, pada MT II tahun 2012 menggunakan lima varietas kontrol, yaitu Mapan P.05, Inpari 13, Dodokan, Ciherang dan Hipa 8 yang ditanam berulang pada tujuh blok dan tiap blok terdiri dari 20 kombinasi padi hibrida. Diperoleh 14 kombinasi padi hibrida yang menunjukkan keragaan yang lebih baik dan memiliki standar heterosis lebih tinggi dari varietas kontrol Ciherang dan Hipa 8. Empat kombinasi hibrida memberikan hasil yang nyata lebih tinggi dibanding Ciherang sebagai varietas pembanding dengan hasil (5,59 t/ha), hibrida tersebut adalah GMJ11/CRS777 (9,1 t/ha), GMJ12/CRS707 (7,6 t/ha), GMJ13/CRS703 (8,7 t/ha), dan GMJ12/CRS795 (7,95 t/ha).